FGFR-targeted therapeutics for the treatment of breast cancer. (4th March 2017) - De Luca, Antonella; Frezzetti, Daniela; Gallo, Marianna; Normanno, Nicola
ABSTRACT: Introduction : Breast cancer is a complex disease and several molecular drivers regulate its progression. Fibroblast growth factor receptor (FGFR) signaling is frequently deregulated in many cancers, including breast cancer. Due the involvement of the FGFR/FGF axis in the pathogenesis and progression of tumors, FGFR-targeted agents might represent a potential therapeutic option for breast cancer patients. Areas covered : This review offers an overview of targeted agents against FGFRs and their clinical development in breast cancer. The most relevant literature and the latest studies in the Clinicaltrial.com database have been discussed. Expert opinion : FGFR inhibition has been recently considered as a promising therapeutic option for different tumor types. However, preliminary results of clinical trials of FGFR inhibitors in breast cancer have been quite disappointing. In order to increase the clinical benefit of FGFR therapies in breast cancer, future studies should focus on: understanding the role of the various FGFR aberrations in cancer progression; identifying potential biomarkers to select patients that could benefit of FGFR inhibitors and developing therapeutic strategies that improve the efficacy of these agents and minimize toxicities.